Balloon Tamponade and Esophageal Stenting for Esophageal Variceal Bleeding in Cirrhosis: A Systematic Review and Meta-analysis - Rodrigues, Susana G.; Cárdenas, Andrés; Escorsell, Àngels; Bosch, Jaime (Seminars in Liver Disease, 2019)
Failure to control variceal bleeding with current recommendations occurs in 10 to 20% of cases. This systematic review and meta-analysis analyzes the experience, results, and complications of “bridge” therapies for failure to control acute variceal bleeding: balloon tamponade and esophageal stents. The main outcomes assessed were failure to control bleeding and mortality in the short-term and medium-term follow-up, and adverse events. Balloon tamponade studies had a pooled rate of short-term failure to control bleeding of 35.5%, and adverse events in over 20% of cases; 9.7% resulting in death. Stenting failed to control bleeding in the short term and medium term in 12.7 and 21.5% of cases of severe or refractory variceal bleeding, respectively, despite stent migration in 23.8% of cases. Medium-term mortality rates were similar in both therapies. Although only one trial compared these treatments, the available evidence consistently supports that stents serve as a better and safer bridge therapy in refractory acute variceal bleeding.
Keywords: cirrhosis; esophageal varices; refractory variceal bleeding; self-expanding metallic stent; Sengstaken-Blakemore tube